A Race for Long Horizon Bankruptcy Prediction - Altman, Edward I.; Iwanicz-Drozdowska, Małgorzata; Laitinen, Erkki K.; Suvas, Arto (Taylor & Francis, 2020)
This study compares the accuracy and efficiency of five different estimation methods for predicting financial distress of small and medium-sized enterprises. We apply different methods for a large set of financial and non-financial variables, using filter and wrapper selection, to predict bankruptcy up to 10 years before the event in an open, European economy. Our findings show that logistic regression and neural networks are superior to other approaches. We document how the cost-return ratio considerably affects the location of optimal cut-off points and attainable profit in credit decisions. Once a loan provider selects a particular prediction model, an effort should be made to find the optimal cut-off score to maximize the efficiency of the technique. Indeed, this often involves determining several cut-off levels where the portfolio of products and services exhibits different cost-return characteristics.
Keywords: cost-return ratio; cut-off; estimation technique; SMEs; variable selection; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|